Public Diplomacy and the Clash of Satellites - Marwa Fikry Abdel Samei (Media and Communication, 2016)
The communication revolution has shifted the paradigm of diplomacy by emphasizing the role of public diplomacy, at the same time complicating the environment within which state-managed public diplomacy is conducted. The rise of regional media has provided weaker states with opportunities to challenge the monopoly of information on the part of the more powerful states. Al-Hurra, the American sponsored channel to the Arab World, stands as evidence of the challenges facing US policies in this part of the world because of the influential role of regional media. It was particularly Al-Jazeera that transformed the media sphere in the Arab World as well as globally in what became known as “Al-Jazeera effect”. The paper argues that identity presentation plays a major role in determining performance of the public diplomacy of the media.